Is Problem Based Learning Assisted by Pop Up Book Effective in Improving Problem Solving Ability and Attitude of Curiosity? - Raden Ajeng Savira Ardani; Lola Pinto Amaral (Elementary Education Journal, 2022)
Backgrounds:. This study aims to determine the effect of the PBL model with the help of pop up book media on the ability to solve problems and the attitude of curiosity in the fourth grade corner material of MIN 2 Sukoharjo (Islamic Elementary School 2 Sukoharjo), Indonesia. Methods:This research uses quantitative research with experimental research design which includes control and experimental classes. The control class uses the thematic learning model, while the experimental class uses the PBL learning model with the help of pop up book media. Data collection techniques through observation, documentation, tests and questionnaires. Data analysis technique using t-test and multiple classification ANOVA test. Results:. Based on the results of data analysis, the value of tcount > ttable was obtained, namely the t-test of 5.14 > 5.14 and 4.37 > 2.04 while the ANOVA test was 2.49 > 2.44. Thus, it can be said that the PBL model assisted by pop up book media has an effect on the ability to solve problems and the attitude of curiosity in the fourth grade corner material of MIN 2 Sukoharjo. Implications:The implications of this research are: First, primary school principals in Indonesia must provide policies that support developing learning models and making learning media more creative and innovative. Second, teachers must provide models and media that are more creative and innovative to overcome the low problem solving abilities and curiosity of students. Novelty:This study reveals the implementation of the influence of the PBL model on problem solving and students' curiosity attitudes.